Antibacterial phenolic compounds from the flowering plants of Asia and the Pacific: coming to the light - Mazdida Sulaiman; Layane behairy; Veeranoot Nissapatorn; Mohammed Rahmatullah; Jhonnel Villegas; Helina Jean Dupa; Ricksterlie C. Verzosa; Karma G. Dolma; Muamad Shabaz; Scholastica Lanting; Nor Azizun Rusdi; Nor Hayati Abdullah; et al. (Taylor & Francis Group, 2024)
Context: he emergence of pan-resistant bacteria requires the development of new antibiotics and antibiotic potentiators. Objective: his review identifies antibacterial phenolic compounds that have been identified in Asian and Pacific Angiosperms from 1945 to 2023 and analyzes their strengths and spectra of activity, distributions, molecular masses, solubilities, modes of action, structures-activities, as well as their synergistic effects with antibiotics, toxicities, and clinical potential. Methods: All data in this review was compiled from Google Scholar, PubMed, Science Direct, eb of Science, and library search; other sources were excluded. e used the following combination of keywords: ‘Phenolic compound’, ‘Plants’, and ‘Antibacterial’. his produced 736 results. ach result was examined and articles that did not contain information relevant to the topic or coming from non-peer-reviewed journals were excluded. ach of the remaining 467 selected articles was read critically for the information that it contained. Results: Out of ~350 antibacterial phenolic compounds identified, 44 were very strongly active, mainly targeting the cytoplasmic membrane of Gram-positive bacteria, and with a molecular mass between 200 and 400g/mol. 2-Methoxy-7-methyljuglone, [6]-gingerol, anacardic acid, baicalin, vitexin, and malabaricone A and B have the potential to be developed as antibacterial leads. Conclusions: Angiosperms from Asia and the Pacific provide a rich source of natural products with the potential to be developed as leads for treating bacterial infections.